Native land claims letters : Nass and Skeena rivers area. - Dalagumook sic , Paul, (Chief); Githemkildo, (Chief); Wegit, Mark, (Chief); Simideak, (Chief); Morgan, Stephen; Tate, C. M.; Indian Brotherhood of British Columbia; Allied Tribes of British Columbia (Simon Fraser University, 1909)
Collection includes 25 items of correspondence from various Chiefs concerning very early land claims in BC. Also illustrate formations of various First Nations organizations over time.